MAJAS PERULANGAN DALAM BUKU ANTOLOGI PUISI GURU “TENTANG SEBUAH BUKU DAN RAHASIA ILMU” SERTA IMPLIKASINYA PADA PEMBELAJARAN SASTRA DI SMA - Ngangga Saputra; Alifiah Nurachmana; Hernika Anja Ratna Putri; Nani Sidarwati; Selvia Sarcie (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
The aims of this study were (1) to describe the types of figurative language that are contained in the Anthology of Teacher's Poems about a Book and the Secrets of Knowledge; and (2) describe the implications for learning literature in high school. This research approach is descriptive qualitative, in line with the findings of the study, namely in the form of a description of the types of figurative language repetition in the Anthology of Teacher's Poetry about a Book and the Secrets of Knowledge and their implications for learning literature in high school. This type of research is qualitative, because the data findings are not obtained by statistical calculations (quantitative) but in the form of phrases, clauses and sentences contained in the Anthology of Teacher's Poems about a Book and Secrets of Knowledge. The results of this study show the following data, namely (1) the figurative language of repetition contained in the Teacher's Poetry Anthology of a Book and the Secret of Knowledge is a repetition of alliteration type of figure of speech consisting of nine quotations, the alliteration figure of speech in these quotations gives rise to an aesthetic impression of the poem. The figure of speech of repetition of the mesodiplosis type has one quote, the figure of speech of mesodiplosis in these quotations emphasizes the meaning of the poem. The figure of speech of repetition which is the type of repetition of five quotations, the figure of speech of repetition in these quotations raises the affirmation of meaning and adds to the aesthetics of the poem. The figure of speech of repetition of the epistrofa type has three quotations. the figure of speech of epistropha in these quotations raises the affirmation of the meaning of the poem, thus the dominant form of repetition used in the Anthology of Guru's Poetry About a Book and the Secrets of Knowledge is a form of repetition of the alliteration type. (2) The implications of the analysis of figurative language in the book Anthology of Teacher Poems About a Book and Secrets of Knowledge for the learning of literature in high school can provide an understanding of the types of figurative language of repetition in a poem. These implications can be used as additional teaching materials to improve students' ability to understand the building blocks of a poem while at the same time creating a work of poetry.